2013
DOI: 10.1097/wad.0b013e318299d28d
|View full text |Cite
|
Sign up to set email alerts
|

Need for and Challenges Facing Functional Communication as Outcome Parameter in AD Clinical Trials

Abstract: This paper (1) highlights the relevance of functional communication as an outcome parameter in Alzheimer disease (AD) clinical trials; (2) identifies studies that have reported functional communication outcome measures in AD clinical trials; (3) critically reviews the scales of functional communication used in recent AD clinical trials by summarizing the sources of information, characteristics, and available psychometric data for these scales; and (4) evaluates whether these measures actually or partially asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…A critical review of existing instruments for assessing communication in people with dementia in terms of an individual's basic skills is given in Haberstroh et al (2013). Besides these instruments, communication skills may be partially assessed when the severity of dementia is measured during diagnostic and therapy processes, for example, by means of the Alzheimer's Disease Assessment Scale (ADAS; Rosen, Mohs, & Davis, 1984), or the Resident Assessment Instrument (RAI 2.0; Morris, Hawes, Murphy, & Nonemaker, 1995).…”
Section: Existing Instruments For Assessing Communication In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…A critical review of existing instruments for assessing communication in people with dementia in terms of an individual's basic skills is given in Haberstroh et al (2013). Besides these instruments, communication skills may be partially assessed when the severity of dementia is measured during diagnostic and therapy processes, for example, by means of the Alzheimer's Disease Assessment Scale (ADAS; Rosen, Mohs, & Davis, 1984), or the Resident Assessment Instrument (RAI 2.0; Morris, Hawes, Murphy, & Nonemaker, 1995).…”
Section: Existing Instruments For Assessing Communication In Dementiamentioning
confidence: 99%
“…International literature offers two main toeholds to be used in the development of assessment instruments on the basis of how communication is theoretically embedded in dementia: (1) communication as a basic skill of an individual, e.g., in functional communication theories (e.g., Bayles & Tomoeda, 1994; Fratalli, Thompson, Holland et al, 1995; Lomas et al, 1989), (2) communication and communication behaviors as essential conditions for constructs like well-being or quality of life in dementia, as observed in certain situational contexts (e.g., Kitwood & Bredin, 1992; Perrin, 1997; Richter, Schwarz, Eisemann, & Bauer, 2003). More information on theories and assessment instruments that focus on basic communication skills can be found in Haberstroh et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…They can cause increased misunderstanding and frustration, gradually leading to restricted social participation of the person with dementia ( Schoenmakers et al, 2010 ), and CCDs have also been found to contribute to caregiver burden ( Stiadle et al, 2014 ). Therefore, there is a growing interest in the development of communication interventions that may prevent or relieve these troublesome effects of CCD ( Barnes & Markham, 2018 ; Williams et al, 2018 ) and subsequently in communication-related measurements that are able to properly evaluate these interventions ( Eadie et al, 2006 ; Haberstroh et al, 2013 ; Williams et al, 2017 ; Williams & Parker, 2012 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…To date, there is a clear lack of suitable tools to measure communication behavior in people with dementia in a differentiated way. A shortcoming is that the existing tools operationalized communication rather as a functional skill and not as a context-dependent behavior related to well-being (for review, see [16]). Furthermore, previous instruments focused more on the verbal content than on the nonverbal relationship aspect.…”
Section: Introductionmentioning
confidence: 99%